lim X tends to 1 , 1-X^-1/3 / 1-X^-2/3
Answers
Step-by-step explanation:
x→1lim1−x−2/31−x−1/3
Here putting the limit x→1 we
get 00 from (undefined form )
None we can apply L-Hospital Rule
⇒x→1limd(1−x−2/3)d(1−x1−/3)
⇒x→1lim0−(3−2x−2/3−1)0−(3−1x−1/3−1) {dxd(xn)=nxn−1=d(x)n
⇒x→1lim+32x−5/3+31x−4/3
⇒x→1lim21x−4/3+35
⇒x→1lim21x31
⇒21(1)1/3⇒21
hope this helps you
its expert in mathematics physics and chemistry
Answer:
Given :-
lim x tends to 1 [1-x^-(1/3)]/[1-x^-(2/3)]
To find:-
Find the value ?
Solution :-
Given that
lim x tends to 1 [1-x^-(1/3)]/[1-x^-(2/3)]
On taking [1-x^-(1/3)]/[1-x^-(2/3)]
We know that a^-n = 1/a^n
=> [1-(1/x⅓)]/[1-(1/x⅔)]
=> [(x⅓-1)/x⅓]/[(x⅔-1)/x⅔]
=> [(x⅓-1)/x⅓] × [x⅔/(x⅔-1)]
=> [(x⅓-1)x⅔] × [x⅓/(x⅔-1)]
=> [(x⅓-1)x⅓] / [(x⅔-1)]
Since a^m / a^n = a^(m-n)
=> [(x⅓-1)x⅓] / [(x⅓)²-1)]
=> [(x⅓-1)x⅓] / [(x⅓)²-1²)]
We know that
(a+b)(a-b) = a²-b²
=> [(x⅓-1)x⅓] / [(x⅓+1)(x⅓-1)]
On cancelling (x⅓-1)
=> (x⅓ / [(x⅓)+1)]
Now,
lim x tends to 1 [1-x^-(1/3)]/[1-x^-(2/3)]
=> lim x tends to 1 [(x⅓ / (x⅓)+1)]
=> 1⅓/(1⅓+1)
=> 1/(1+1)
=> 1/2
Answer:-
The value of the given problem is 1/2.